Optical coupling in dielectric resonator nanoantenna - Malheiros-Silveira, Gilliard Nardel [UNESP]; Hernandez-Figueroa, Hugo Enrique (Optica Publishing Group, 2018)
A theoretical study regarding to coupling efficiency between a dielectric resonator nanoantenna (DRNA) integrated to a metal-dielectric-metal-dielectric nanostrip waveguide (NW), and free space is evaluated.